(untitled) (International Seven Journal of Multidisciplinary, 2024)
Aging brings some limitations that are accentuated with advancing age, and psychological, physical, behavioral and social changes can reduce the quality of life of the elderly, who seek spirituality. Spirituality is a tool for coping with difficulties and assigning meaning to life, providing hope, faith, and motivation. This study analyzed the health aspects associated with spirituality in community-dwelling older adults. This is an integrative review that synthesized the scientific production with the guiding question: What is the production of scientific knowledge about health-related aspects associated with better levels of spirituality in community-dwelling older adults in Brazil? Articles with the descriptors in Portuguese and English were selected: spirituality, elderly, quality of life with the following inclusion criteria: published in full, available electronically, in Portuguese, English and/or Spanish, published between 2015 and 2020, in the SciELO, LILACS, PubMed and Capes Journal Portal databases. A total of 130 articles were identified, and 15 were selected that presented evidence on the influence of spirituality on the quality of life of the elderly. After reading the articles, two categories of analysis emerged: I – The experience of spirituality in situations of chronic diseases, and II – The relationship between spirituality and the well-being/quality of life of the elderly. Most studies have shown positive effects of spirituality on health outcomes, with better physical health conditions, quality of life, longer survival, lower rates of depression and lower prevalence of chronic diseases. In addition to demonstrating the ability to withstand limitations, protect from stress in the face of aging changes. Finally, the results indicate a positive influence of spirituality on the quality of life of the elderly. The importance of spirituality for health practices and the need to value and include it in professional health training are highlighted.